Optimalisasi Kepuasan dan Produktivitas Kerja Karyawan Melalui Pendekatan Insentif dan Teknik Manajemen Stres yang Efektif pada Perusahaan Starup Teknologi Indonesia - Elli Sulistyaningsih (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Incentive approaches and effective stress management techniques, technology startup companies in Indonesia can increase the productivity of their employees. Employees will be more motivated, more high-performing, and produce better results. Through an incentive approach and effective stress management techniques, technology startup companies can create a work environment that allows employees to feel satisfied and productive. Satisfied and productive employees can contribute to improving company performance and achieving long-term success. The results of the correlation analysis between compensation and employee performance of 0.809 indicate a significant and very strong relationship. Work stress with employee performance of 0.680 shows a significant and strong relationship. Job satisfaction with employee performance shows a significant and very strong relationship with a correlation value of 0.786. In this study, a combined incentive approach and effective stress management techniques can significantly increase employee satisfaction and work productivity in Indonesian technology startup companies.